La Vaccination Contre la Grippe Saisonnière Faut-Il L’imposer a L’ensemble de la Population Algérienne?: Approche par L’économie de la Prévention - Benhamouda, Youcef; Khelifa, Hadj (جامعة محمد بوضياف المسيلة - كلية العلوم الاقتصادية والتجارية وعلوم التسيير, 2022)
Background: Through this study, we wish to identify the characteristics that indicate the individuals likely to have complications linked to seasonal influenza and to use these characteristics to make a decision concerning the obligation to vaccinate all or a particular part of the Algerian population. Method: To answer this problem, we have built a model using the technique of artificial neural networks (ARN) which is widely used as a decision support tool and especially in areas where expertise is necessary for adequate decision-making. Results: the model showed that the effectiveness of vaccination was very high and that the age category is an essential factor in defining the population concerned by the obligation to vaccinate. Conclusion: he study concluded that all people aged 50 and over should be vaccinated regardless of whether they have chronic diseases or not.
Keywords: الأمراض الوبائية -- الإنفلونزا الموسمية -- التطعيمات الوقائية -- الرعاية الصحية